Chemical Profile Determination and Quantitative Analysis of Components in Oryeong-san Using UHPLC-Q-Orbitrap-MS and UPLC-TQ-MS/MS - Seol Jang; Ami Lee; Youn-Hwan Hwang (Molecules, 2023)
In this study, a method to both qualitatively and quantitively analyze the components of Oryeong-san (ORS), which is composed of five herbal medicines (Alisma orientale Juzepzuk, Polyporus umbellatus Fries, Atractylodes japonica Koidzumi, Poria cocos Wolf, and Cinnamomum cassia Presl) and is prescribed in traditional Oriental medicine practices, was established for the first time. First, ORS components were profiled using ultra-high-performance liquid chromatography/quadrupole Orbitrap mass spectrometry, and 19 compounds were clearly identified via comparison against reference standard compounds. Subsequently, a quantitative method based on ultra-high-performance liquid chromatography coupled with triple-quadrupole tandem mass spectrometry was established to simultaneously measure the identified compounds. Nineteen compounds were accurately quantified using the multiple-reaction-monitoring mode and used to analyze the sample; we confirmed that coumarin was the most abundant compound. The method was validated, achieving good linearity (R2 ≤ 0.9991), recovery (RSD, 0.11–3.15%), and precision (RSD, 0.35–9.44%). The results suggest that this method offers a strategy for accurately and effectively determining the components of ORS, and it can be used for quality assessment and management.